Interacting and joint effects of triglyceride-glucose index and body mass index on future endometrial cancer risk and the mediating role of body mass index: a cross-sectional study - Wang, Yixiao; Kong, Wenzhi; Geng, Yuning; Xu, Chunyu; Miao, Jinwei (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose (TyG) index, a promising biomarker for insulin resistance, is linked to the risk of various metabolic-related cancers. However, to date, data on the association of TyG index with different subtypes of endometrial cancers and the potential mediating role of clinical factors remain limited.MethodologyData was collected from the Beijing Obstetrics and Gynecology Hospital, Capital Medical University spanning from 2014 to 2024. Female participants with complete data on the TyG index were included in the analysis. Multivariate logistic regression analyses were used to assess the association of TyG index with endometrial cancer risk, adjusted by series of confounders. Mediation effects were evaluated using Valeri and VanderWeele’s method.ResultsA total of 1,194 eligible participants were enrolled, with 597 (50%) women diagnosed with endometrial cancer. The fully adjusted multivariate logistic regression model revealed a significant association between the TyG index and the risk of endometrial cancer (odds ratio [OR]Tertile 3 versus Tertile 1: 1.93, 95% confidence interval [CI]: 1.37–2.73; P for trend=0.028). Notably, BMI exhibited significant mediation effects on this association, even after adjusted by potential confounders (P for trend<0.001). The proportion of the effect mediated by BMI was 25% in the crude analysis (95% CI: 0.15, 0.37; P<0.001) and increased to 41% in the adjusted analysis (95% CI: 0.24, 0.76; P<0.001). However, no correlation was found between TyG index and the clinical characteristics of endometrial cancer (P>0.05). Moreover, BMI is associated with the risk of different endometrial cancers.ConclusionThis cross-sectional study demonstrated that a higher TyG index, representing higher level of insulin resistance, was associated with a higher risk of endometrial cancer. Importantly, we found that BMI acted as a significant mediator in this relationship. Prospective studies are needed to further validate these findings.